(untitled) (Hekima Review, 2008)
This article examines the growing phenomenon of cohabitation, especially in urban settings. It also explores the Church’s position on the issue, linking it with the high premium the Church places on the institution of marriage. The author then proffers suggestions for dealing with the problem pastorally.